The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1007/s00401-023-02593-x
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral myeloid-derived suppressor cell-like cells are closely related to the clinical severity of multiple sclerosis

Abstract: Multiple sclerosis (MS) is a highly heterogeneous demyelinating disease of the central nervous system (CNS) that needs for reliable biomarkers to foresee disease severity. Recently, myeloid-derived suppressor cells (MDSCs) have emerged as an immune cell population with an important role in MS. The monocytic-MDSCs (M-MDSCs) share the phenotype with Ly-6Chi-cells in the MS animal model, experimental autoimmune encephalomyelitis (EAE), and have been retrospectively related to the severity of the clinical course i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In the experimental autoimmune encephalomyelitis (EAE) model, MDSCs can trigger T cell apoptosis to suppress inflammation and boost recovery of EAE symptoms ( 52 ). Similarly, the abundance of Monocytic MDSC in blood samples from untreated MS patients at the time of first relapse had a negative correlation with the EDSS at baseline and after one-year follow-up ( 53 ), underscoring the need for dynamic MDSC monitoring in the development of MS.…”
Section: Discussionmentioning
confidence: 99%
“…In the experimental autoimmune encephalomyelitis (EAE) model, MDSCs can trigger T cell apoptosis to suppress inflammation and boost recovery of EAE symptoms ( 52 ). Similarly, the abundance of Monocytic MDSC in blood samples from untreated MS patients at the time of first relapse had a negative correlation with the EDSS at baseline and after one-year follow-up ( 53 ), underscoring the need for dynamic MDSC monitoring in the development of MS.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the transplantation of IMCs could offer a neuroprotective strategy worth contemplating, especially if we consider that their immunoregulatory potency is acquired and enhanced by inflammation [ 79 ]. In addition, it has very recently been shown that MDSCs exert an important immunosuppressive effect over both activated T and B cells [ 80 ]. For all these reasons we did not apply any type of immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fifteen studies investigating the MDSC expansion in MS, two were conducted in human subjects [43,44], three used both human subjects and a mouse model [45][46][47], eight were performed in a mouse model [15,[48][49][50][51][52][53][54], and two in vitro, using MDSCs isolated from MS patients or a mouse model of MS [55,56]. The investigations on MDSC-targeting treatment were carried out in murine models or in vitro cells collected from MS patients or EAE animals.…”
Section: Mdscs In Multiple Sclerosismentioning
confidence: 99%
“…In RRMS, both M-and PMN-MDSC subsets are increased during the relapse with respect to the remitting phase and healthy subjects [43][44][45]47]. Moreover, the greater the number of M-MDSCs in the relapse phase, the faster the recovery.…”
Section: Mdscs In Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation